Clinical application of magnetic anchor technique in laparoscopic cholecystectomy: the first retrospective study in China - Tian, Boyan; Zhang, Miaomiao; Ren, Yuxiang; Zhang, Yuhan; Lyu, Yi; Yan, Xiaopeng (Frontiers in Surgery, 2024)
Background and objectives: Magnetic anchor technique (MAT) is frequently used in laparoscopic cholecystectomy. However, there are few reports on its clinical application in China. In this study, we retrospectively analyzed the clinical application of MAT in laparoscopic cholecystectomy in China. Materials and methods: 25 patients (4 males, 21 females) who underwent laparoscopic cholecystectomy assisted by MAT at the First Affiliated Hospital of Xi’an Jiaotong University were enrolled from November 2020 to March 2021. Their records were retrospectively analyzed. The magnetic anchor device was independently designed and developed by the authors and consisted of the anchor magnet and magnetic grasping apparatus. Surgical time, intraoperative blood loss, intraoperative accidents, operator experience, postoperative incision pain score, postoperative complications, and other indicators were evaluated and analyzed. Results: All patients successfully underwent laparoscopic cholecystectomy, including 3 cases of MAT-assisted transumbilical single-port LC, 16 cases of MAT-assisted 2-port LC and 6 cases of conventional 3-port LC. The median operation time was 50 min (range 30-95 min); intraoperative bleeding was less than 30 ml. The median score of surgical incision on day 1 and 3 after the operation was 3 (range 1-4) and 1 (range 1-3), respectively. All patients had no intraoperative bile duct injury, vascular injury, postoperative bleeding, bile leakage, biliary stricture and other complications. No adverse events (such as injury to adjacent organs or failure of the magnetic anchor device) occurred either during or after the operation. Conclusions: The MAT-assisted laparoscopic cholecystectomy appears to be safe, feasible and effective and exhibits unique assistance in transumbilical single-port laparoscopic cholecystectomy.